PKM. PENANAMAN KARAKTER MELALUI PEMBELAJARAN DAN EKSTRAKURIKULER PADA SISWA SMK PGRI 1 BADUNG - I Putu Karpika; Luh Putu Swandewi Antari; I Ketut Suardana; I Made Gede Putra Wijaya (LP3M Universitas PGRI Mahadewa Indonesia, 2024)
Education at school is not enough just to teach students to read, write and count, then pass exams and later get a good job. However, schools must be able to educate students to be able to decide what is right and wrong. Education is carried out in schools with the hope of developing thinking abilities while forming good student character to achieve life goals in life. The aim of this service is to find solutions on how to instill character education through scout extracurricular activities and classroom learning for students at SMK PGRI 1 Badung. To achieve this goal, students must instill character-forming values ​​originating from religion, Pancasila and culture. The method used in this service is training and mentoring with three stages, namely the preparation stage, activity stage, and activity evaluation stage. The results of the implementation of scouting activities at SMK PGRI 1 Badung went well and this activity was attended by all students and scout leaders by paying attention to the basic principles and methods of scouting. The characters that emerge in the implementation of character education are discipline, caring for the environment, tolerance, communicative, religious, democratic, curious, self-confident, creative, independent, hard working, responsible, honest, socially concerned, and appreciate achievement. Likewise, education carried out at school can develop thinking abilities as well as shape students' good character to achieve life goals in life.